WOJNA HYBRYDOWA JAKO NOWY RODZAJ KONFLIKTU ZBROJNEGO WE WSPÓŁCZESNYM ŚWIECIE - JAKUBIAK Ewa (2022)
It has been over eight years since the Russian Federation illegally conquered Crimea. It was probably the apogee of the biggest noise about the "Russian hybrid war". Some authors in the literature on the subject have completely questioned this concept, while others have perceived it as a new way of waging war. In recent years, hybrid war has become a new but controversial term in academic, political book positions to suggest a kind of combination of different military and non-military means and methods. The ongoing war conflict in Ukraine has shown the important role played by well-organized propaganda. It must not be forgotten that one of the most important goals of contemporary hybrid wars is to win a battle in the enemy's mind. In order to achieve this, it is necessary to have a free media market, in which the aggressor occupies a strong position or such a level of access to modern telecommunications technologies among the population of the attacked state, which will allow for widespread familiarization with propaganda and information materials posted on social networks, websites. The aim of the article is to present the issue of hybrid warfare in the modern world .Given the vastness and depth of Messner's insights, his work could be expected to occupy a more prominent place in all analyses and discussions related to the “Russian hybrid warfare”. This is especially true in comparison to the noise surrounding the article (which is also very interesting) written by Russian General Gerasimov in 2013 on the tendency to blur the boundaries between states of war and peace.The formula of the hybrid warfare in eastern Ukraine and the Gerasimov doctrine launched a discussion on the military power of Russia, the state and significance of conventional forces, the ability to project strength, the state and scope of non-military instruments that, as part of the synergy effect, may support military ones, with particular emphasis on the role of propaganda.